Assessing Complex Working Memory in Turkish-Speaking Children: The Listening Span Task Adaptation Into Turkish - Ünal, Gülten; Özge, Duygu; Marinis, Theodoros (Frontiers in Psychology, 2020)
The aim of this study was to adapt the Listening Span Task (Gaulin and Campbell, 1994; Pickering and Gathercole, 2001) into Turkish (LST-T), to administer it to children in order to measure how children of different ages perform on the task and to measure its psychometric properties by providing correlations with other cognitive measures: the Word Span Test that measures phonological WM capacity, the Wisconsin Card Sorting Test that measures both categorization ability and executive WM functions, and the Categorical Free Recall Test that examines both the development of the release from proactive interference pattern and the categorization ability during childhood. The results indicate that the LST-T scores increased in a significant stepwise manner without any gender difference between boys and girls. Measures of convergent validity showed significant correlations with the two working memory tests: the Word Span Test, and the Wisconsin Card Sorting Test. The results demonstrate that the LST-T is an adequate tool to be used by developmentalists for a variety of purposes, ranging from developmental research to educational and clinical practice to investigate cognitive development of Turkish-speaking children.